Rate of employment after liver transplantation in France: a single-centre study. Issue 2 (February 2016) - Rudler, Marika; Rousseau, Géraldine; Lebray, Pascal; Méténier, Océane; Vaillant, Jean-Christophe; Savier, Eric; Eyraud, Daniel; Poynard, Thierry; Thabut, Dominique
Abstract : Background: A return to gainful employment is an important outcome parameter after liver transplantation (LT). A recent study in the USA has shown a very high rate of unemployment after LT (75%). To date, there are no available data in France, where the public health insurance programme guarantees financial protection for everyone. Aims: The aim of this study was to assess the employment rate after LT in a French LT centre and to determine factors associated with employment after LT. Methods: All patients who had undergone liver transplantation at our centre between January 2000 and April 2011 and who met the following criteria responded to a questionnaire: (i) between 18 and 65 years old at the time of LT, (ii) alive 1 year after LT, (iii) alive, not retired and released from the hospital at the time of survey, (iv) French residents who were affiliated with French national health insurance. Results: A total of 345 LTs were performed in 314 patients during the study period. Of the patients, 109 were excluded from the study: 23 had died within the first year after LT, 28 had died at the time of the survey, three were still in the hospital, seven were living in a foreign country, 11 had retired and 37 were older than 65 years after LT. Two hundred five patients were included in the study. The response rate was 76.6% (157/205). Patients responded a mean 6.1±0.9 years after LT, 77.7% were French nationals, 73.2% were men, and the mean age at LT was 48.8±9.9 years. The aetiologies of liver disease were as follows: alcohol 32.5%, hepatitis C 26.1%, alcohol and hepatitis C 3.8%, hepatitis B 15.3%, biliary cirrhosis 5.1%, autoimmune 2.5% and other causes 14.7%. Two years after LT, 43.3% of patients were employed. The demographic variables associated with post-LT employment were male sex ( P <0.001), age under 40 years at LT ( P =0.02), a sedentary job ( P =0.007), raising children under the age of 18 years at the time of LT ( P =0.01), a high level of education ( P =0.001), not being affiliated with the French universal health coverage or 'CMU' ( P =0.001). Only 53.3% of the patients who did not return to work after LT stated that they felt like they had a physical disability. Conclusion: The rate of return to work after LT in France was 43.1%, which was higher than that reported in the US study. However, this rate remains low and policies supporting return to work are needed to help liver recipients who wish to work after LT.